Propriedade Alternada do Operador de Dirichlet-Neumann - Silva, José Eduardo Jesus da (2010)
In this work we talk about properties of the Dirichlet-to-Neumann map for the conductivity equation in a smooth manifold with boundary of R2. We use several times the Maximum Principle to conclude a Alternating Property of the Dirichlet-to- Neumann map. Using this property, we and that the Kernel satises a given set of inequalities. Finally, we note that these inequalities imply the Alternating Property of the Kernel of the Dirichlet-to-Neumann map.